Prognostic value of optical flow ratio for cardiovascular outcomes in patients after percutaneous coronary stent implantation - Tianyu Hu; Qinghua Qiu; Nianjin Xie; Mingming Sun; Qianjun Jia; Meiping Huang (Frontiers in Cardiovascular Medicine, 2023)
BackgroundThe relationship between the optical flow ratio (OFR) and clinical outcomes in patients with coronary artery disease (CAD) after percutaneous coronary stent implantation (PCI) remains unknown.ObjectiveTo examine the correlation between post-PCI OFR and clinical outcomes in patients with CAD following PCI.MethodsPatients who underwent optical coherence tomography (OCT) guided PCI at Guangdong Provincial People's Hospital were retrospectively and continuously enrolled. Clinical data, post-PCI OCT characteristics, and OFR measurements were collected and analyzed to identify predictors of target vessel failure (TVF) after PCI.ResultsAmong 354 enrolled patients, 26 suffered TVF during a median follow-up of 484 (IQR: 400–774) days. Post-PCI OFR was significantly lower in the TVF group than in the non-TVF group (0.89 vs. 0.93; P = 0.001). In multivariable Cox regression analysis, post-PCI OFR (HR per 0.1 increase: 0.60; 95% CI: 0.41–0.89; P = 0.011), large stent edge dissection (HR: 3.85; 95% CI: 1.51–9.84; P = 0.005) and thin-cap fibroatheroma (TCFA) (HR: 2.95; 95% CI: 1.19–7.35; P = 0.020) in the non-stented segment were independently associated with TVF. In addition, the inclusion of post-PCI OFR to baseline characteristics and post-PCI OCT findings improved the predictive power of the model to distinguish subsequent TVF after PCI (0.838 vs. 0.796; P = 0.028).ConclusionThe post-PCI OFR serves as an independent determinant of risk for TVF in individuals with CAD after PCI. The inclusion of post-PCI OFR assessments, alongside baseline characteristics and post-PCI OCT findings, substantially enhances the capacity to differentiate the subsequent manifestation of TVF in CAD patients following PCI.